2013
DOI: 10.1002/jeab.19
|View full text |Cite
|
Sign up to set email alerts
|

A Derived Transfer of Eliciting Emotional Functions Using Differences Among Electroencephalograms as a Dependent Measure

Abstract: Emotional responses have specific electroencephalographic (EEG) signatures that arise within a few hundred milliseconds post-stimulus onset. In this experiment, EEG measures were employed to assess for transfer of emotional functions across three 3-member equivalence classes in an extension of Dougher, Auguston, Markham, Greenway, & Wulfert's (1994) seminal work on the transfer of arousal functions. Specifically, 12 human participants were trained in the following match-to-sample performances A1 = B1, A2 = B2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
2
22
0
2
Order By: Relevance
“…Continuing along the line of some recent findings (e.g., Amd & Roche, 2015;Silveira et al, 2015), emotional TOF studies using faces have highlighted the importance of membership within newly established relational structures (versus preexisting ones; see Lakens, Semin, & Foroni, 2012) in manipulating stimulus valence (Amd & Roche, 2016). This is why blurred faces were employed as stimuli in the present study, given previous findings showing happiness/valence TOF effects as most pronounced when emotionally masked faces are embedded in relational structures (Amd, 2014;Amd & Roche, 2015; but see Amd, Barnes-Holmes, & Ivanoff, 2013, for a non-face-related exception). This may have to do with the conspecific nature of faces, which humans can discriminate accurately from early in life (e.g., Bonatti, Frot, Zangl, & Mehler, 2002).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Continuing along the line of some recent findings (e.g., Amd & Roche, 2015;Silveira et al, 2015), emotional TOF studies using faces have highlighted the importance of membership within newly established relational structures (versus preexisting ones; see Lakens, Semin, & Foroni, 2012) in manipulating stimulus valence (Amd & Roche, 2016). This is why blurred faces were employed as stimuli in the present study, given previous findings showing happiness/valence TOF effects as most pronounced when emotionally masked faces are embedded in relational structures (Amd, 2014;Amd & Roche, 2015; but see Amd, Barnes-Holmes, & Ivanoff, 2013, for a non-face-related exception). This may have to do with the conspecific nature of faces, which humans can discriminate accurately from early in life (e.g., Bonatti, Frot, Zangl, & Mehler, 2002).…”
supporting
confidence: 64%
“…In Amd and Roche's (2016) study, stimulus-elicited FAAs appeared sensitive to the newly established valence gradients for the stimuli in the series. Given that FAAs can differentiate between valenced stimuli in humans from as early as two years of age (Davidson & Fox, 1989) and are arguably less broad in scope (Briesemeister et al, 2013, but see ) than other EEG metrics of valence (such as event-related potentials; see Amd et al, 2013;Patel & Azzam, 2005), the authors concluded that the observed FAA gradients might be reflective of derived valence TOFs.…”
Section: Assessing Tof Through Contextually Controlled Transitive Infmentioning
confidence: 99%
“…That is, RFT predicts that the Bhappiness^functions of the A-B-C-D stimuli would differ along a comparative dimension A>B>C>D, where A would be the happiest and D the least happy. In other words, the functions of the stimuli would transform in accordance with the entailed relations (Amd and Barnes-Holmes 2014;Amd et al 2013;De Almeida and de Rose 2015;Dougher et al 1994Dougher et al , 2002Munnelly et al 2010;Roche and Dymond 2008).…”
mentioning
confidence: 99%
“…Assim, os resultados obtidos não poderiam ser atribuídos a um efeito de condicionamento avaliativo. Por outro lado, estudos sobre transferência de função têm demonstrado várias evidências de que estímulos equivalentes se tornam substituíveis uns aos outros, podendo evocar diferentes tipos de respostas, inclusive emocionais (e.g., Amd, Barnes-Holmes, &, 2013;Bortoloti & de Rose, 2009de Almeida & de Rose, 2015;de Rose et al, 1988;Dougher et al, 1994;Wulfert & Hayes, 1988). Pesquisas sobre medo e ansiedade, por exemplo, têm mostrado que o medo evocado por um membro da classe pode se transferir para outros membros (e.g., Bennett, Meulders, Baeyens, &Vlaeyen, 2015;Dymond, Dunsmoor, Vervliet, Roche, & Hermans, 2015), um efeito também chamado de generalização simbólica ou baseado em categorias.…”
Section: Discussionunclassified
“…Várias pesquisas têm demonstrado que se as relações entre os estímulos da classe são de equivalência, a atribuição de uma função a um membro desta classe é transferida para os demais (e.g., Amd, Barnes-Holmes, & Ivanoff, 2013; Barnes-Holmes, Barnes-Holmes, Smeets, Luciano, 2004;de Rose, McIlvane, Dube, Galpin, & Stoddard, 1988;Dougher, Augustson, Markham, Greenway, & Wulfert, 1994;Wulfert & Hayes, 1988). Dougher et al (1994), por exemplo, pareou um membro de uma classe (CS) com choque elétrico leve (US) que eliciou uma resposta galvâni-ca da pele (GSR).…”
unclassified